Impact de la situation linguistique minoritaire sur les soins de santé pour les personnes âgées francophones de l’Ontario souffrant de maladies chroniques : partage des connaissances et rétroaction. Rapport de recherche - Lemonde, Manon; Boudreau, Françoise; Dufour, Suzanne (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Étude exploratoire : perceptions, croyances, connaissances et attitudes d’un groupe d’aînés francophones du Nouveau-Brunswick concernant la démence et son diagnostic - Pakzad, Sarah; Paulin, Marie-Claire; Jbilou, Jalila; Fontaine, Véronique; Bourque, Paul-Émile; Bélanger, Mathieu; Routhier, Nicholas; Lavoie, Anne Marise (Reflets, 2012)
Cette étude explore les perceptions, croyances, connaissances et attitudes d’un groupe d’aînés francophones du Nouveau-Brunswick face à la démence et à son diagnostic; le diagnostic précoce de la démence est crucial autant pour l’identification des causes réversibles que pour la mise en place rapide d’interventions de prévention secondaire. Quatre-vingt-onze francophones du Nouveau-Brunswick âgés de 65 ans et plus ont été interrogés face à la démence et à son diagnostic dans cette étude quantitative exploratoire. Entre autres, bien que les participants de cette étude aient rapporté avoir peur de recevoir un diagnostic de démence, la plupart voudraient recevoir le diagnostic s’ils en étaient atteints. Les résultats soulignent l’importance d’éduquer la population face à la démence et aux services d’évaluation de la démence. D’autres implications sont discutées. Mots-clés : Démence, diagnostic, intention, maladie d’Alzheimer, minorité linguistique

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.